Responsabilidade social corporativa na indústria têxtil e de confecção: comparativo entre Brasil e China - Castro, Felipe de (2010)
New demands and greater pressure for transparency in business conduct force companies to adopt a more responsible posture regarding their actions, which caused the textile and apparel production to start realizing their responsibilities towards the society and the environment. The work is classified as exploratory and descriptive. The research is characterized as a fieldwork. As for its nature, it was used a quantitative and qualitative method in the research, which combines the statistical analysis of the survey application to investigate the meaning of human relations of the interviews to compare and discuss the quantitative and qualitative researches. This research establishes a tool to assess the Brazilian and Chinese textile and apparel industries comparing its practices regarding Corporate Social Responsibility (CSR). The instrument of quantitative research was based on the application of a Corporative Responsibility awareness survey. A survey procedure was utilized in which a structured questionnaire was given to 45 managers working in textile and apparel industries in the Brazilian states of São Paulo and Ceará, and in the Chinese cities of Beijing, Shanghai, and Guangzhou. At the same time, interviews were conducted aiming to access the chosen group perceptions regarding the corporative social responsibility in the textile and apparel industry in both Brazil and China. Five main practices were investigated: market policies, policies relating to work locations, environmental policies, policies related to the community, and business values. The interviews were conducted with a group of stakeholders in the textile and apparel sectors from China and Brazil, including purchasing directors, trading managers, the Associação Brasileira da Indústria Têxtil - ABIT (Brazilian Association of the Textile Industry), and the Câmara de Comercio e Indústria Brasil China - CCIBC (Brazil-China Industry and Commerce Chamber). The data collected with the questionnaires were analyzed using descriptive statistics and mean test, and for the interviews a technique of content analysis was adopted. The results found show that the practices of corporate social responsibility are still incipient in the textile and apparel industry both in Brazil and in China, that either countries have no policies aiming the social and environmental development, and that these countries only satisfy their market and own government requirements.